Google Classroom Application to Improve Student Learning Activity - Heri Slamet Riyadi (Universitas Sebelas Maret, 2020)
This study aims to describe the application of the Google Classroom Application in an Effort to Improve Learning Activeness of Class VI Odd Semester Students of SDN Gebang 1. This classroom action research lasts for three cycles, each cycle consisting of four stages, namely planning, implementing, observing, and reflecting. Student activity in the first cycle with good categories was 70.8%. In the second cycle with good categories as much as 87.5%. In the third cycle students with good categories were 100%. Compared to cycle 1, student learning activities in cycle III have increased by 29.2%. Based on this, it proves that the application of the google classroom application can improve student learning activities in the theme of 5 entrepreneurship class VI SD Gebang 1 Bonang.